An experimental study of the agglomeration of coal fines in suspensions: Inspiration for controlling fines in coal reservoirs. (1st January 2018) - Shi, Qingmin; Qin, Yong; Zhou, Binyang; Zhang, Minjian; Wu, Meng; Wang, Lina
Highlights: Fine coal particles easily agglomerate to migrate and plug flow paths in CBM reservoirs. Dispersive tiny fines agglomerate into several ranges of aggregations that are larger than 10 μm. Coal-fine agglomerations in deionized, standard saline and NaHCO3 suspensions were analysed. Agglomerations of bituminous coals are more sensitive to suspensions than those of anthracites. Abstract: Coal fines are among the key issues that restrict the highly efficient production of coalbed methane (CBM) because they cause blockages in reservoirs and accidents in wellbores. Coal fines always agglomerate to migrate and plug flow paths in formation water. Therefore, an investigation of their agglomerate behaviour in deionized, standard saline and NaHCO3 suspensions was conducted on different rank coals (81.95 and 92.22% Cdaf) collected in the Ordos and Qinshui basins. The particle size distributions (PSD) of the suspended coal fines in suspensions over time were monitored to analyse the sizes and number of aggregations using a particle size analyser. The dispersive coal fines that were mostly less than 10 μm in size aggregated into several ranges of aggregations larger than 10 μm in a rapid process until reaching a stable period of sedimentation, inducing the average sizes of the suspended particles to increase rapidly and their quantities to suddenly decrease. As observed under a scanning electron microscope, the dispersive fine particles, which had quasi-ellipsoid, plate and flake shapes, clustered together. The average sizes of the suspended particles in the NaHCO3 suspensions were the greatest, and their quantities were the smallest after the rapid agglomeration, exhibiting a capacity for agglomeration somewhat better than that in the standard saline suspensions and much better than that in the deionized suspensions. The PSD differences of the suspended bituminous coals in the three suspensions were more remarkable than those for anthracites because the former, which had higher ζ potentials measured using a microscopic electrophoresis instrument, were more easily impacted by different types of ions. Bituminous coal has more oxygen-containing functional groups than anthracite, which forms thicker hydration layers that prevent coal fines from agglomerating. According to extended DLVO (Derjguin-Landau-Verwey-Overbeek) theory, cations (Na + and H + ), especially H + ionized by HCO3 −, can neutralize the charge of electrical double-layers and help coal fines to agglomerate. In addition, OH − hydrolysed by HCO3 − can reduce the viscosity of suspensions. Therefore, in CBM reservoirs, NaHCO3 may fix some portions of coal fines at their sources by agglomeration and contribute to the other fine particles migration by reducing the viscosity. NaHCO3 may be a potential additive in fracturing fluid, which needs to be further researched.